A Mathematical Model for the Dimensioning of Combined Footings of Rectangular Shape - Luévanos Rojas, Arnulfo (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
This paper presents a mathematical model to obtain the most economical dimension of the contact surface in combinedÂ footings of rectangular shape subjected to an axial load and moment in two directions (bidirectional bending), when the loadÂ that must support said structural member is applied. The cases presented in this paper are: 1) Combined footings of boundary;Â 2) Combined footings intermediate. The classic model considers an axial load and a moment around the axis “X” (transverse axis)Â applied to each column, i.e., the force resulting from the applied loads are located on the axis “Y” (longitudinal axis), and onceÂ obtained the resultant force and its position is necessary to adjust the length thereof such that the centroid of loads coincidesÂ with the geometrical center. The main part of this research is that the proposed model considers the bending moments aroundÂ the axis “Y” and the classic model neglected the moments around the axis Y”. Then, the proposed model is more suited to heÂ general conditions and is more economical.